Do accountants make better chief financial officers? - Hoitash, Rani; Hoitash, Udi; Kurt, Ahmet C. (Journal of Accounting and Economics, 2016)
We examine whether chief financial officers (CFOs) with accounting backgrounds (accountant CFOs) are associated with more conservative corporate outcomes. We find that, in high-growth industries, firms with accountant CFOs invest less in research and development and capital expenditures and are less likely to engage in external financing. In low-growth industries, we find that firms with accountant CFOs exhibit greater cost efficiency. Our results are consistent with risk aversion on the part of accountant CFOs. We further document that accountant CFOs are negatively associated with firm value in high-growth industries and positively associated with firm value in low-growth industries.